Efficacy of Focal Photocoagulation to Maintain or Achieve Best Corrected Visual Acuity ≥20/40, in Eyes with Diabetic Macular Edema - Dulce, Milagros Razo-Blanco-Hernandez; Diana, Alejandra Bermudez-Zapata; Sandra, Marieli Romo-Rodriguez; Virgilio, Lima-Gomez (Journal of Bioinformatics And Diabetes, 2015)
Objective: To identify the efficacy of focal photocoagulation to maintain or achieve best corrected visual acuity (BCVA) ≥20/40 in eyes with clinically significant macular edema (CSME) that had a focal angiographic pattern. Material and Methods: Non-experimental, retrospective, longitudinal, descriptive study in type 2 diabetic patients of any gender, who had CSME with focal angiographic pattern, who received focal photocoagulation from January to October 2012, with a register of BCVA before and 3 weeks after photocoagulation. 101 eyes from patients aged 35-74 years (mean 60.1±8.15) were assigned to one of two groups: 1, with BCVA before treatment <20/40 (n=60), and 2, with BCVA ≥20/40 (n=41). The proportion of eyes with BCVA≥20/40 after treatment was identified, in the sample and within each group. Results: In group 1 BCVA improved in 34 eyes (56.7%), did not change in 15 (25%), and worsened in 11 (18.3%); in group 2 BCVA improved in 10 eyes (24.4%), did not change in 18 (43.9%) and worsened in 13 (31.7%). Post treatment BCVA was ≥20/40 in 57 eyes (56.4%, 95% confidence intervals 46.8-66.1%), 21 of them from group 1 (36.8%) and 36 from group 2 (63.2%). Conclusion: Treating CSME with focal photocoagulation was efficacious to maintain BCVA ≥20/40 in 87.8% of eyes with that rank of vision preoperatively, and to achieve BCVA ≥20/40 in 35% of eyes without it. Early detection and treatment of CSME is required to increase the proportion of eyes with BVCA that provides visual independence, preferably when visual function is still good.
Keywords: Diabetic retinopathy; clinically significant macular edema; moderate visual loss; best corrected visual acuity.